Auto–transition in RADG based on chaotic system - Kadhum, Laith M.; Zainal Abidin, Ahmad Firdaus; Zolkipli, Mohamad Fadli; Hisham, Syifak Izhar; Bayuaji, L.; Ab Razak, Mohd Faizal (College of Education, Al-Iraqia University, 2023)
The RADG (Reaction Automata Direct Graph) cryptosystem is the automata direct graph and reaction states combination. The classical RADG does not require key exchange (keyless), or agreement between users just the design of RADG, which is static. The RADG algorithm with keys has two agreements between users, one is on the keys, and other is a design of RADG. The RADG design depends on states and transitions between them, since transitions between states are static transitions, or dynamic transitions have agreement between users to determine the type of state (Jump state, Reaction state) of RADG algorithm with keys, and the transition between states must cover each states scenario of RADG design .This article presents algorithm called (Auto- Transition Function (ATF)), which merge properties of RADG algorithm with chaotic system to obtain on transitions between states are automatic. The parameters of ATF are chaotic initial value, parameter of chaotic function, and characteristics of RADG, then ATF is an auto creation of transitions among all states in RADG, and it satisfies each scenario of RADG design.